THE ROLE OF DIGITAL TECHNOLOGIES IN INCREASING THE EFFICIENCY OF PUBLIC ADMINISTRATION - Rustam Mamatov (Modern American Journals, 2025)
This article focuses on analyzing the impact of digital transformation on public administration processes. It explores how the integration of digital technologies can enhance the efficiency of public services, reduce bureaucratic barriers, ensure transparency, and improve interaction between government institutions and the public. Particular attention is paid to the current challenges faced by Uzbekistan in the transition to a digital public administration system, along with proposed solutions and strategic approaches. The paper highlights the potential of emerging technologies such as artificial intelligence, big data, and blockchain in reforming and modernizing governance. Practical examples are provided to illustrate how these technologies can be applied to optimize decision-making, automate routine administrative tasks, and foster citizen-centric governance. Furthermore, the study offers insights into the institutional, technical, and legal prerequisites for successful digital transformation. The findings of this research aim to serve as a basis for formulating effective policy measures and strategic directions to support the digital modernization of public administration. Ultimately, the paper contributes to the broader discourse on e-governance and the digital state, emphasizing the importance of innovation, infrastructure, and human capital in building a more responsive and accountable public sector.
Keywords: Digital transformation, public administration, e-governance, artificial intelligence, big data, blockchain, transparency, efficiency, Uzbekistan, digital public services.